Twitter as a mirror of political space(s): An analysis of multi-level party competition in Italy - Camatarri, Stefano; Gallina, Marta; Anselmi, Guido; Schadee, Henri M. A.; Segatti, Paolo (Regional & federal studies, 2023)
The literature on the nationalization of party systems has found that decentralization of authority leads to increasing territorial heterogeneity of voting behaviour. In this article, we intend to further extant knowledge on this topic by exploring whether different levels of government imply distinct representations of party competition at the citizens' level. We do so by analysing Twitter data collected during the 2015 regional elections in five Italian regions (Liguria, Veneto, Tuscany, Campania and Apulia) to estimate national and regional party configurations by means of multi-dimensional scaling. Analyses show that national party competition is generally perceived in the same way across regions, but representations of regional political spaces tend to stand out from it and also to differ from each other. These results suggest that, in line with the process of political decentralization of authority, voters perceive party competition in different ways according to the level of territorial governance at stake.